Harmonic analysis based method for linearity assessment and noise quantification in electrochemical impedance spectroscopy measurements: Theoretical formulation and experimental validation for Tafelian systems. (1st September 2016) - Giner-Sanz, J.J.; Ortega, E.M.; Pérez-Herranz, V.
Abstract: Electrochemical Impedance Spectroscopy (EIS) is an electrochemical measurement technique that has been applied to a broad range of applications. Three conditions must be fulfilled in order to obtain valid EIS measurements: causality, linearity and stationarity. The non fulfilment of any of these conditions may lead to distorted and biased EIS spectra. Consequently, the verification of the four fundamental conditions is mandatory before accepting any results extracted from an EIS spectrum. In this work, a harmonic analysis based method for linearity assessment and noise quantification in EIS measurements is presented, and validated both from an experimental point of view and from a theoretical point of view, for Tafelian systems. It was shown that the presented method was able to quantitatively assess the nonlinearity of the system; and to quantify and characterize the noise. Moreover, the presented method is able to determine the threshold frequency of the system above which the system does not present significant nonlinear effects even for very large perturbation amplitudes.